1984
DOI: 10.1042/bj2230455
|View full text |Cite
|
Sign up to set email alerts
|

Radioassay of UDP-glucuronyltransferase-catalysed formation of bilirubin monoglucuronides and bilirubin diglucuronide in liver microsomes

Abstract: A radioassay for specific determination of the rates of UDP-glucuronic acid-dependent conversion of bilirubin into the two isomeric (C-8, C-12) bilirubin monoglucuronides and bilirubin diglucuronide is described and illustrated by its application to rat liver microsomes. The method is based on measurement of the relative amounts of radiolabel in unesterified bilirubin and its mono- and di-esterified reaction products after incubation with [14C]bilirubin as substrate. This analysis is performed by the alkaline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…4.8 zero-order kinetic conditions the diglucuronide amounted to 22-23% of the rate of formation of the total BMG (Table 1). These results are in agreement with those obtained in previous work (Blanckaert et al, 1979;Gordon et al, 1983;Vermeir et al, 1984). Further, the initial rates of formation of the two isomeric (C-8, C-12) BMGs by these microsomal preparations indicated that the C-8 isomer was produced approximately twice as rapidly as the C-12 isomer (Table 1), confirming previous work of Blanckaert et al (1979).…”
Section: Results and Discussion Enzyme Purification And Bilirubin Glusupporting
confidence: 92%
See 2 more Smart Citations
“…4.8 zero-order kinetic conditions the diglucuronide amounted to 22-23% of the rate of formation of the total BMG (Table 1). These results are in agreement with those obtained in previous work (Blanckaert et al, 1979;Gordon et al, 1983;Vermeir et al, 1984). Further, the initial rates of formation of the two isomeric (C-8, C-12) BMGs by these microsomal preparations indicated that the C-8 isomer was produced approximately twice as rapidly as the C-12 isomer (Table 1), confirming previous work of Blanckaert et al (1979).…”
Section: Results and Discussion Enzyme Purification And Bilirubin Glusupporting
confidence: 92%
“…Chemicals and reagents were as described elsewhere (Burchell, 1977(Burchell, , 1980; the preceding paper, Vermeir et al, 1984), except when stated otherwise in the text. The UDP-sugars were purchased from Sigma (St. Louis, MO, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…911 Radioassays have been used to quantify antigens at sub-pM concentrations, drugs such as buprenorphine at sub-nM concentrations, 1, 8 and enzyme activity. 45…”
Section: Introductionmentioning
confidence: 99%
“…Radionuclides, specifically 3 H, 33 P, and 35 S (all β-particle emitters), are commonly used as labels in biological assays due to the distribution of these atoms in biological systems. Unlike fluorophores or fluorescent protein tags, radionuclides do not significantly increase the size or mass of the labeled component and therefore have minimal effects on binding, conformational changes, diffusion and active transport, etc. In addition, lower backgrounds are typically obtained for radioassays compared to fluorescence assays, where background arises from the inherent fluorescence of many species within the sample. Radioassays have been used to quantify antigens at sub-pM concentrations, drugs such as buprenorphine at sub-nM concentrations, , and enzyme activity. , …”
Section: Introductionmentioning
confidence: 99%